MENINGKATKAN PRODUKTIVITAS USAHA MELALUI MOTIVASI - Andi Marlinah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2009)
Productivity means the comparison between the output and the input, while the motivation is the inisiative process done by the aware action to achieve the purpose . Most researchers of motivation have develop different theories to predict motivation, one of the theories that has been developed is expectancy theory regarded as the best tool which explains that human behaviour is influenced by probability attached by someone to the company needed to achieve the purpose, performance and esteem which satisfy personal aim. So, principally the motivation is given by company in any form, it means to increase employees’ poductivity.